2022
DOI: 10.1152/physiol.00025.2021
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Impact of Hypothermia: The Good, the Bad, and the Ugly

Abstract: Hypothermia is defined as a core body temperature of < 35°C, and as body temperature is reduced the impact on physiological processes can be beneficial or detrimental. The beneficial effect of hypothermia enables circulation of cooled experimental animals to be interrupted for 1-2 h without creating harmful effects, while tolerance of circulation arrest in normothermia is between 4 and 5 min. This striking difference has attracted so many investigators, experimental as well as clinical, to this field, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 215 publications
0
14
0
Order By: Relevance
“…For the surgical treatment of complex heart abnormalities, due to the complicated operation, the large trauma to the patient, the long cardiopulmonary bypass time, and the need to maintain a long-term deep hypothermia state, the damage to the brain is relatively severe. One-third of children with complex congenital (116)(117)(118). Studies have reported that the incidence of epilepsy after surgery for children with congenital heart abnormalities is 4% to 10%, and the incidence of epilepsy after surgery for complex congenital heart abnormalities is even higher (113).…”
Section: Interventions For Congenital Heart Abnormalities and Brain D...mentioning
confidence: 99%
See 1 more Smart Citation
“…For the surgical treatment of complex heart abnormalities, due to the complicated operation, the large trauma to the patient, the long cardiopulmonary bypass time, and the need to maintain a long-term deep hypothermia state, the damage to the brain is relatively severe. One-third of children with complex congenital (116)(117)(118). Studies have reported that the incidence of epilepsy after surgery for children with congenital heart abnormalities is 4% to 10%, and the incidence of epilepsy after surgery for complex congenital heart abnormalities is even higher (113).…”
Section: Interventions For Congenital Heart Abnormalities and Brain D...mentioning
confidence: 99%
“…Deep hypothermic circulatory arrest is commonly used in open heart surgery for complex congenital heart abnormalities. In the state of deep hypothermic circulatory arrest, the energy metabolism of the brain is depleted, causing brain damage through mechanisms such as calcium overload and excitatory amino acid toxicity ( 116 118 ). Studies have reported that the incidence of epilepsy after surgery for children with congenital heart abnormalities is 4% to 10%, and the incidence of epilepsy after surgery for complex congenital heart abnormalities is even higher ( 113 ).…”
Section: Interventions For Congenital Heart Abnormalities and Brain D...mentioning
confidence: 99%
“…Our aim is to update the readers on physiological changes occurring in various organ systems, as a knowledge basis for rewarming victims of AH and HCA. Although the topic recently was reviewed by one of us, the different emphasis should make this paper be considered as complementary ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, currently used hypothermia triggered by peripheral cold sensors is ineffective in lowering the core body temperature ( T core ) to the desired level 13 , 15 . The cooling process also evokes vigorous counteractive shivering thermogenesis that is difficult to tolerate in awake patients 16 , 17 , and produces harmful side effects to the heart, lungs, and brain 9 . A better method to induce therapeutic hypothermia is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular cascades that set in after cerebral ischaemia are complex [2][3][4][5] , which hamper the development of neuroprotective therapies. Hypothermia at mild to moderate levels (31-34 °C) during or following cerebral ischaemia is powerful neuroprotective [6][7][8][9][10][11][12] . Hypothermia can simultaneously inhibit multiple mechanisms of brain cell death and slow down metabolic processes to limit tissue damage 10,13,14 , providing additive or synergistic beneficial clinical effects for stroke patients.…”
mentioning
confidence: 99%